Relationship Between Reading Habits, Interests, and Reading Comprehension Abilities of Islamic Elementary School Students - Fajri, Zaenol; Nuraini, Ryan (Jurnal Kiprah Pendidikan, 2025)
One of the key literacy abilities that must be acquired starting in elementary school is reading comprehension.  However, a problem at Islamic Elementary School is the children's poor reading habits and lack of enthusiasm.  The purpose of this study is to ascertain how students' reading comprehension abilities relate to their hobbies and reading habits at the same time.  Thirty-fourth and fifth-grade children at MI Mirqotul Ulum Probolinggo participated in the study, which used a quantitative approach with a correlational method and purposive sampling.  SPSS version 25 was used to evaluate the instruments, which took the form of reading comprehension exams and surveys.  The findings demonstrated that the data were normally distributed and that the instruments were both valid and dependable.  Reading habits and interests were significantly correlated with reading comprehension skills, according to multiple regression tests (correlation coefficient 0.882 and significance 0.000).  These results underline the importance of an interesting and long-lasting literacy program and support constructivism theory and other studies.  It is advised that future research incorporate a larger range of respondents and take into account additional external factors like the involvement of parents and the learning environment, as this study is constrained in terms of sample size and geography